Il virus influenzale: una nuova pandemia dietro l’angolo? - Concetta Castilletti; Maria Rosaria Capobianchi (Microbiologia Medica, 2006)
Differently from other viral diseases, like measles, smallpox and polyomielitis, influenza is caused by a virus that undergoes continuous antigenic changes, and has several animal reservoirs. Influenza virus is an enveloped virus, with a segmented negative RNA strand genome, belonging to the family Orthomyxoviridae. Influenza viruses are grouped in three different genotypes:A, B and C. Only genotype A viruses are able to cause relevant outbreaks, and are capable of infecting both humans and animal species. Antigenicity of surface glycoproteins (hemagglutinin, HA, and neuraminidase, NA) stimulate a protective immune response. The emergence of small antigenic changes determined on HA and NA by point mutations (antigenic drift) is on the basis of the seasonal outbreaks, whose spread is allowed by the incomplete protection provided by immunity against the previous infecting viral strains.The reassortment of genome segments that may occur after mixed infection with different antigenic types is on the basis of the appearance of new antigenic combinations (antigenic shift), leading to the emergence of vaste outbreaks, possibly involving most of the human world population (pandemics). Two classes of drugs are available against influenza: inhibitors of viral entry into the host cell and inhibitors of viral release (neuraminidase inhibitors).As a common phenomenon accompanying the usage of selective drugs, the emergence of resistant viral strains is a problem that is to be considered when planning the large use of antiviral drugs to restrict the spread of a possible pandemic. The recent appearance of a paper describing the complete sequence of the virus causing the tremendous pandemic called “spanish flu” in 1918, and of a paper reporting the in vitro reconstruction of this virus through reverse genetic methods, raised some concern about the possibility that the new information could be used in an offensive way by bioterrorists. On the other hand, thanks to these scientific achievements, the first steps have been accomplished towards the elucidation of pathogenic mechanisms underlying the high pathogenicity of this virus, so rendering more realistic the possibility of preparing appropriate tools to cope with the next pandemic expected to be behind the corner.